Timing is everything: the role of contextual and terrorism-specific factors in the sentencing outcomes of terrorist offenders - Amirault, Joanna (European journal of criminology, 2017)
The punishment of terrorist offenders remains a relatively unexplored topic. Research is especially needed in the United Kingdom in light of the continued criminalization of terrorism-specific offences and the July 2005 bombings. Using a sample of terrorist offenders convicted in the United Kingdom (n = 156), the current study examines the impact of legislative and incident-based contextual factors on sentencing outcomes. The findings indicate that changing contextual environments significantly affect sentencing outcomes, and that the effects of being adjudicated at different time points have unique implications for offenders motivated by an Islamic extremist ideology. Further, evidence of a temporal effect is uncovered, and the potential of a lingering 9/11 effect is addressed.